Glucocorticoids in IgA vasculitis - Armağan, Berkan (Acta Medica, 2024)
IgA vasculitis (IgAV) is an immune complex vasculitis affecting small vessels characterized by IgA1 immune deposits. IgA vasculitis typically resolves spontaneously in most cases, especially in pediatric cases but may have more severe outcomes in adults and the optimal treatment for IgAV remains controversial. Although glucocorticoids are the mainstay of treatment, studies are investigating the role of alternative immunosuppressive agents and biologics, particularly in adult onset, severe or resistant cases. The efficacy of glucocorticoids appears to vary according to the specific manifestations and severity of IgAV. They may be effective in treating complications when combined with immunosuppressive agents but glucocorticoids should not be used prophylactically as they do not prevent complications.